‘My maine hope is, to begin the sport at Millaine’: Italy in Philip Massinger’s The Duke of Milan - Paravano, Cristina (Early Theatre, 2023)
Philip Massinger’s The Duke of Milan (1621) clearly sits in the tradition of the Elizabethan and Jacobean Italianate tragedy and is resonant of stories, ideas, theories, and characters from Italian history and its literary tradition. This essay discusses the play as one of the earliest examples of Massinger’s interest in Italy and its culture. It investigates the play’s Italian setting and examines the influence of the Italian cultural and political legacy to offer new insights into the development of Anglo-Italian relations and England’s home and religious politics in the early 1620s.